2016
DOI: 10.1002/apj.2057
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the behavior of high‐viscosity fluids falling film flow down the vertical wavy wall

Abstract: Falling film flow with high‐viscosity fluid is used throughout in the process intensification of industry production. However, analysis of wave characteristics based on operational conditions and independent of the geometrical wall is seriously restricted to low‐fluid viscosity. A general predictability of dynamic flow behavior of highly viscous fluid falling film flow is lacking. Our work has been motivated by such a challenge. Numerical simulations of gravity‐driven two‐dimensional steady falling film flow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Such technique overcomes the limitations of melt polycondensation due to the rate of glycol removal from high‐viscosity molten polymers, can produce PET with a high IV of 1.0 dL g −1 . When the IV of PET increases from 0.65 to 1.0 dL g −1 in this technique, the strength of the corresponding filament increases about twice and it has become particularly useful in the manufacture of PET industrial yarns …”
Section: Introductionmentioning
confidence: 99%
“…Such technique overcomes the limitations of melt polycondensation due to the rate of glycol removal from high‐viscosity molten polymers, can produce PET with a high IV of 1.0 dL g −1 . When the IV of PET increases from 0.65 to 1.0 dL g −1 in this technique, the strength of the corresponding filament increases about twice and it has become particularly useful in the manufacture of PET industrial yarns …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sinusoidal corrugation and a novel design consisting of isolated semicircular bumps distanced by the wavelength of the surface waves were verified to have better heat and mass transfer compared with the flat wall 33 . Chen et al 34 numerically studied the film flow on the vertical wave plate with high‐viscosity fluids. They found that the flow behavior of high‐viscosity fluids is partly different from that of low‐viscosity fluids.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of high-viscosity fluids (1.5–210 Pa·s) was employed by Xi et al, who considered the falling film flow in a grid falling film tower and suggested that the falling film form can be used in polymer melt devolatilization and polymer reaction engineering. Chen et al , designed wave structures of different sizes on vertical tubes to drive the lateral disturbance of high-viscosity fluids (0.92–623 Pa·s) in the falling film flow, proving that the high-viscosity fluids flow on the wave structure not only has a high film-forming effect but also significantly improves the sufficient surface renewal frequency, which is more conducive to heat and mass transfer. In brief, the patterns of falling film flow in the cases of high-viscosity fluids are not as rich as the patterns of low-viscosity fluids; unique and valuable flow characteristics still exist that deserve further study.…”
Section: Introductionmentioning
confidence: 99%